BIOLOGICAL DECOLORIZATION OF CARCINOGENIC AZO DYE: AN ECOFRIENDLY APPROACH - MERINA PAUL DAS; MANAS BHOWMICK; MAGGIDI REYNOLDS (International Journal of Pharma and Bio Sciences, 2016)
Dyes are extremely used in textile, leather, paper industries for colorations. But unsafe disposal of these dyes into the environment causes serious damage and negative effect to the human, plant and animal health. Microbial decolorization is a low cost and is frequently applied process for the decolorization of textile dyes. Methyl red (MR) is a carcinogenic textile dye which is used for the coloration of various products. The objective of the study was to isolate the active bacterial strains which can decolorize the azo dye Methyl red. Among thirteen isolates, four potential bacteria (MR-1, MR-2, MR-3, MR-4) with methyl red decolorizing ability were selected for identification and used for the decolorization process. All the four microorganisms showed maximum dye degradation after 48 h of incubation. The improvement of the decolorization of methyl red was obtained by optimization of various nutritional and environmental factors for each isolate. The results from this study show the potential and practical applications of these bacterial isolates to treat the textile effluent containing MR dye.